Medical nutrition therapy administered by a dietitian yields favourable diabetes outcomes in individual with type 2 diabetes mellitus - Mohd Yusof, Barakatun Nisak; Abd Talib, Ruzita; Abdul Karim, Norimah; Kamaruddin, Nor Azmi (Malaysian Medical Association, 2013)
This prospective, single-group, pre-post design trial was conducted to evaluate the effect of individualised Medical Nutrition Therapy intervention administered by a dietitian in individuals with type 2 diabetes mellitus on glycaemic control, metabolic parameters and dietary intake. Subjects (n=104; age=56.4 ±9.9 years; 37% male; years of diagnosis = 6.3 ±4.9 years) treated with diet and on a stabile dose of oral anti-diabetic agents were given dietary advice by a dietitian for a 12 week period. Individualised dietary advice was based on Malaysian Medical Nutrition Therapy for adults with type 2 diabetes mellitus. The primary outcome measure was glycaemic control (fructosamine and HbA1c level) and the secondary outcome included measures of anthropometry, blood pressure, lipid profile, insulin levels dietary intake and knowledge on nutrition. At week 12, 100 subjects completed the study with a dropout rate of 3.8%. The post-Medical Nutrition Therapy results showed a significant reduction of fructosamine (311.5 ±50 to 297 ±44 umol/L; P< 0.001) and HbA1c (7.6 ±1.2 to 7.2 +1.1%, p<0.001) with pronounced reduction for subjects who had very high HbA1c levels of >9.3% at baseline. Waist circumference (90.7 ±10.2 to 89.1 ±9.8 cm, p<0.05), HDL-cholesterol (1.1 ±0.3 to 1.2 ±0.3 mmol/L, p<0.05), dietary intake and nutrition knowledge score (42 ±19 vs. 75 ±17%; p< 0.001) were significantly improved from the baseline. Individualised Medical Nutrition Therapy administered by a dietitian resulted in favourable diabetes outcomes, which were more apparent for individuals with higher than optimal HbA1c levels at the start of the study.